Web service discovery: Reality check 2.0 - Stephan Hagemann; Carolin Letz; Gottfried Vossen (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2007)
In practice the ability to find the right Web service decides between a functionality being implemented anew and at least the possibility of executing it via a service. This report evaluates existing public portals for Web service discovery with respect to their characteristics and their acceptance by developers. For this, we distinguish different possible settings and use cases and evaluate how these are supported in practice. Only few of the publicly available Web service registries are growing in size and importance, with the use case best supported being the pre-programming phase of evaluation of the service landscape.
Keywords: 650; Web services; Web service discovery; UDDI; public service directories; Web 2.0